2021
DOI: 10.2196/28896
|View full text |Cite
|
Sign up to set email alerts
|

Team Building Through Team Video Games: Randomized Controlled Trial

Abstract: Background Organizations of all types require the use of teams. Poor team member engagement costs billions of US dollars annually. Objective This study aimed to explain how team building can be accomplished with team video gaming based on a team cohesion model enhanced by team flow theory. Methods In this controlled experiment, teams were randomly assigned to a team video gaming treatment or a control treatm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Regarding primary fit, this is indicated by synchronized movements of group members during group flow (Gloor et al, 2013) and a high positive correlation between group flow and emotional synchrony (Zumeta, Oriol, et al, 2016). In terms of secondary fit, this is indicated by a group-level balance of challenges and skills being present together with facets of a group state of mind (Keith et al, 2021). Moreover, there is strong evidence that group flow is dynamic (e.g., Armstrong, 2008; ad Proposition 4).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Regarding primary fit, this is indicated by synchronized movements of group members during group flow (Gloor et al, 2013) and a high positive correlation between group flow and emotional synchrony (Zumeta, Oriol, et al, 2016). In terms of secondary fit, this is indicated by a group-level balance of challenges and skills being present together with facets of a group state of mind (Keith et al, 2021). Moreover, there is strong evidence that group flow is dynamic (e.g., Armstrong, 2008; ad Proposition 4).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Social involvement, furthermore, to functional efficacy, raises user pleasure (Kujur, 2017). Players frequently talk to their peers about their mobile gaming experiences and even form gaming teams (Keith et al, 2021). There are concerns about internet interactions between mobile game players, for instance, cheering and commentary analysis from teammates that can improve team spirit.…”
Section: Social Influence and Customer Satisfactionmentioning
confidence: 99%
“…In addition, a web-based emergency room game for interprofessional education improved teamwork attitudes among medical and nursing students [ 41 ]. Moreover, Keith et al [ 42 ] found that playing video games as a team improved team performance, probably related to team cohesion processes. However, robust studies on game effectiveness and design choices are still inconclusive owing to the low quality of the evidence and paucity of studies included in meta-analyses [ 43 - 45 ].…”
Section: Introductionmentioning
confidence: 99%